Brain Computed Tomography Angiography as an Ancillary Test in the Confirmation of Brain Death - Sadeghian, Homa (Cureus, 2017)
Introduction Brain death (BD) is the irreversible termination of the functioning of the brain. The diagnosis should be first made by clinical criteria and confirmed by using paraclinical confirmatory techniques (ancillary tests). While conventional brain angiography remains the standard method of choice, computed tomography angiography (CTA) has emerged as an alternative method. In this study, we tried to evaluate the accuracy of CTA for the diagnosis of BD. Methods In this study, we included nine patients with a clinical diagnosis of BD, confirmed by electroencephalography (EEG). CTA was then performed to compare the results. Results The most frequent cause for BD was multiple trauma (7/9) in our patients, followed by aneurysm rupture and brain infarct. CTA examination in all patients showed opacification of extracranial arteries and major branches of external carotid artery (ECA), including superficial temporal arteries (STAs), while no opacification was observed in the internal carotid arteries (ICA) including and beyond the cavernous segment, middle cerebral arteries (MCAs), anterior cerebral arteries (ACAs), distal vertebral arteries (VAs), and basilar artery (BA). Moreover, no opacification was observed in the internal cerebral veins (ICVs) or great cerebral vein (GCV). Conclusion The accuracy rate of CTA in the detection of intracranial circulatory arrest was 100%. CTA examinations confirmed BD diagnoses in all patients who had clinical and EEG BD diagnoses, and no confliction between CTA findings and clinical diagnoses was observed.